Tocantins river as an effective barrier to gene flow in Saguinus niger populations - Marcelo Vallinoto; Juliana Araripe; Péricles S. do Rego; Claudia H. Tagliaro; Iracilda Sampaio; Horacio Schneider (Genetics and Molecular Biology, 2006)
The Saguinus represent the basal genus of the Callitrichinae subfamily. Traditionally this genus is divided into three groups: Hairy, Mottled and Bare-face, however, molecular data failed to validate these groups as monophyletic units, as well as raised some subspecies to the species status. This is the case of the former subspecies Saguinus midas midas and S. midas niger, which are now considered as different species. In the present study, we sequenced a portion of the D-loop mtDNA region in populations from the East bank of the Xingu and from both banks of the Tocantins river, in order to test the effectiveness of large rivers as barriers to the gene flow in Saguinus. According to our results, the populations from the East and West banks of the Tocantins river are more divergent than true species like S. mystax and S. imperator. The Tocantins river may be acting as a barrier to gene flow, and consequently these very divergent populations may represent distinct taxonomic entities (species?).